Heroines without Heroes : Reconstructing Female and National Identities in European Cinema, 1945-51. - Siehlohr, Ulrike (Film Studies: Bloomsbury Academic Collections., 2016)
"This anthology explores a little-examined period of European film history (1945-1951) and places gender at the centre of struggles around national identity. Ulrike Sieglohr compares and contrasts the post-war cinemas of Britain, France, Germany, Italy, and Spain in order to examine how representations of women in this period emerged from specific national contexts. She further analyzes the appeal of particular stars and the political and social conditions that contributed to their popularity."--